An implementation of ultrasonic water meter using dToF measurement. Issue 1 (1st January 2017) - Lee, Chul-Ho; Jeon, Hye-Kyung; Hong, Youn-Sik
Abstract: A method of the ultrasonic transmission time difference (ToF) flow measurement is the one which is mainly applied to large diameter flow meters by incorporating high power digital signal processing devices. In this paper, we propose a ToF-type ultrasonic water meter which can be applied to small diameter flow meters such as water meters at home. Unlike the existing ToF method, a differential ToF (dToF) algorithm is proposed to calculate the flow rate irrespective of the water temperature. We have also focused on low-power design by minimizing the computational portion of the micro-controller. To do this, a measuring principle using dToF has been implemented with a single front-end chip and a single MCU.